Leveraging Patient-Reported Outcomes Using Data Visualization - Grossman, Lisa V.; Feiner, Steven K.; Mitchell, Elliot G.; Masterson Creber, Ruth M. (Applied Clinical Informatics, 2018)
Background Health care organizations increasingly use patient-reported outcomes (PROs) to capture patients' health status. Although federal policy mandates PRO collection, the challenge remains to better engage patients in PRO surveys, and ensure patients comprehend the surveys and their results.Objective This article identifies the design requirements for an interface that assists patients with PRO survey completion and interpretation, and then builds and evaluates the interface.Methods We employed a user-centered design process that consisted of three stages. First, we conducted qualitative interviews and surveys with 13 patients and 11 health care providers to understand their perceptions of the value and challenges associated with the use of PRO measures. Second, we used the results to identify design requirements for an interface that collects PROs, and designed the interface. Third, we conducted usability testing with 12 additional patients in a hospital setting.Results In interviews, patients and providers reported that PRO surveys help patients to reflect on their symptoms, potentially identifying new opportunities for improved care. However, 6 out of 13 patients reported significant difficultly in understanding PRO survey questions, answer choices and results. Therefore, we identified aiding comprehension as a key design requirement, and incorporated visualizations into our interface design to aid comprehension. In usability testing, patients found the interface highly usable.Conclusion Future interfaces designed to collect PROs may benefit from employing strategies such as visualization to aid comprehension and engage patients with surveys.
Keywords: data visualization; consumer health informatics; human–computer interaction; patient-reported outcomes; patient engagement; interfaces and usability